The Effects of Prenatal Diagnosis on the Interaction of the Mother–Infant Dyad: A Longitudinal Study of Prenatal Care in the First Year of Life - de Souza, Vera Cristina Alexandre; Parlato-Oliveira, Erika; Anchieta, Lêni Márcia; Machado, Alexei Manso Correa; Savelon, Sylvie Viaux (Frontiers in Psychology, 2022)
Introduction Mother–child interactions during the first years of life have a significant impact on the emotional and cognitive development of the child. In this work, we study how a prenatal diagnosis of malformation may affect maternal representations and the quality of these early interactions. To this end, we conducted a longitudinal observational study of mother–child interactions from the gestational stage until the baby completed 12 months of age. Participants and Methods We recruited 250 pregnant women from a local university hospital. Among them, 50 mother–infant dyads participated in all stages of the study. The study group consisted of 25 pregnant women with fetuses with some structural alteration and the control group consisted of 25 pregnant women with fetuses without structural anomalies. We collected obstetric and socio demographic data and pregnancy outcomes. Anxiety and depressive state data were collected using the COVI and Raskin Scales. We video-recorded the mother–infant interactions during several stages, including when the child was a newborn and when the child was 2, 4, 6, 9, and 12 months of age. The quality of the mother infant interactions were measured using the Coding Interactive Behavior (CIB). The interactive moments recorded on video was composed of three different activities, each one lasting appoximately 3 min, which included (1) Free Interaction, where the mother was instructed to interact “as usual” without any toy, (2) Toy Interaction, where the mother and baby played with a puppv, and (3) Song Interaction, where the mother and baby interacted while the mother sang the “Happy Birthday” song. Results In the gestational phase, there was a significant difference between the groups with respect to anxiety and depression scores, which were significantly higher for the study group. In the postnatal phase, we found significant differences between the groups with respect to CIB scales after the child completed 6 months of age: the study group presented significantly higher values of Maternal Sensitivity at 6 months of age, of Baby Involvement at 9 and 12 months of age, and of Dyadic Reciprocity at 6, 9, and 12 months of age, while the control group presented significantly higher values of Withdrawal of the Baby at 6 months of age, and of Dyadic Negative States at 6 and 9 months of age. Conclusion The support offered by the study favored the mother–infant bond and had a positive effect on the quality of interaction during the first year of life, despite the presence of prenatal diagnosis.